Psychiatric taxonomy: at the crossroads of science and ethics - Tekin, Şerife (Journal of medical ethics, 2014)
The scientific investigation of mental disorders is an invigorating area of inquiry for philosophers of mind and science who are interested in exploring the nature of typical and atypical cognition as well as the overarching scientific project of ‘carving nature at its joints’. It is also important for philosophers of medicine and bioethicists who are concerned with concepts of disease and with the development of effective and ethical treatments of mental disorders and the just distribution of mental health services. Philosophical worries surrounding mental health and its care have recently extended beyond the bounds of academia, becoming a vigorous topic of debate in a variety of public domains in the wake of the publication of the most recent revision of the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5), the psychiatric classification system used by mental health professionals in the USA, and increasingly, by those around the world.The DSM-5 lists mental disorders according to the observable symptoms presented by patients. It is designed for pragmatic use across a variety of settings to accomplish several tasks: to facilitate clinical treatment, to provide clear criteria of eligibility for various administrative and policy related purposes (such as the determination of insurance coverage and disability aid (p. xxiii;1 p.xli2)), and primarily, to further scientific research into mental disorder aetiology. Although designed to meet the needs and interests of various stakeholders (including patients and their families, researchers, clinicians and insurance companies), the recently revised manual has not fully satisfied any of them. This failure challenges the assumption that a single manual …